ASSESSMENT OF CHLORIDE ION POLLUTION OF SMALL RIVERS IN THE NIZHNEVARTOVSK REGION - Alagulov, Denis Andreevich; Ivanova, Angelina Vyacheslavovna (Siberian Journal of Life Sciences and Agriculture, 2020)
The importance in assessing the environmental situation in the Khanty-Mansi Autonomous Okrug is represented by the concentration of chemicals in surface waters and bottom sediments, which characterize the technogenic flows of pollutants in the areas of oil fields. Chloride pollution of small rivers leads to their accumulation in bottom sediments. High concentrations of chloride ions in surface waters and bottom sediments adversely affect the river ecosystem. Важное значение в оценке экологической ситуации в Ханты-Мансийском автономном округе представляют концентрации химических веществ в поверхностных водах и донных отложениях, которые характеризуют техногенные потоки загрязняющих веществ в районах нефтепромыслов. Хлоридное загрязнение малых рек приводит к их накоплению в донных отложениях. Высокие концентрации хлорид-ионов в поверхностных водах и донных отложениях негативно воздействуют на речную экосистему.